Macrophysical properties of tropical cirrus clouds from the CALIPSO satellite and from ground‐based micropulse and Raman lidars. Issue 16 (28th August 2013) - Thorsen, Tyler J.; Fu, Qiang; Comstock, Jennifer M.; Sivaraman, Chitra; Vaughan, Mark A.; Winker, David M.; Turner, David D.
Abstract : [1] Lidar observations of cirrus cloud macrophysical properties over the U.S. Department of Energy Atmospheric Radiation Measurement (ARM) program Darwin, Australia, site are compared from the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite, the ground‐based ARM micropulse lidar (MPL), and the ARM Raman lidar (RL). Comparisons are made using the subset of profiles where the lidar beam is not fully attenuated. Daytime measurements using the RL are shown to be relatively unaffected by the solar background and are therefore suited for checking the validity of diurnal cycles. RL and CALIPSO cloud fraction profiles show good agreement while the MPL detects significantly less cirrus, particularly during the daytime. Both MPL and CALIPSO observations show that cirrus clouds occur less frequently during the day than at night at all altitudes. In contrast, the RL diurnal cycle is significantly different from zero only below about 11 km; where it is of opposite sign (i.e., more clouds during the daytime). For cirrus geometrical thickness, the MPL and CALIPSO observations agree well and both data sets have significantly thinner clouds during the daytime than the RL. From the examination of hourly MPL and RL cirrus cloud thickness and through the application of daytime detection limits to all CALIPSO data, we find that the decreased MPL and CALIPSO cloud thickness during the daytime is very likely a result of increased daytime noise. This study highlights the significant improvement the RL provides (compared to the MPL) in the ARM program's ability to observe tropical cirrus clouds and will help improve our understanding of these clouds. The RL also provides a valuable ground‐based lidar data set for the evaluation of CALIPSO observations. Key Points: The MPL detects far fewer cirrus compared to the RL/CALIPSO The RL is relatively unaffected by the increased daytime noise CALIPSO and MPL cirrus are biased thin (geometrically) during the daytime